Effect of Cracks on the Compressive Ultimate Strength of Plate and Stiffened Panel Under Biaxial Loads: A Finite Element Analysis - Sang Jin Kim; Jung Min Sohn; Do Kyun Kim (Applied Sciences)
Crack damage can significantly reduce the ultimate strength of marine structures, potentially leading to progressive collapse. This study employs finite element analysis to investigate how cracks affect the strength of plates and stiffened panels under uniaxial and biaxial compression, providing insights essential for robust structural design. The effects of crack size and orientation are explored through a systematic evaluation of longitudinal, transverse, and bidirectional cracks—sized at 10%, 25%, and 50% of structural dimensions (plate length and plate breadth/web height)—in both plates and unstiffened panels. The analysis identifies key parameters governing strength degradation and reveals that stiffened panels are more resistant to cracking, whereas plates are more sensitive to crack orientation and loading direction. These findings underscore the role of crack characteristics and structural reinforcement in maintaining residual strength and provide guidance for improving the accuracy and reliability of ultimate strength predictions.